Botany in five senses: the sensorial garden as an instrument to raise awareness about the importance of botany in schools in a municipality in the Piauí state (Research, Society and Development, 2021)
The benefits of sensory gardens extend far beyond the aesthetic and recreational dimensions, constituting an important element of learning, coexistence, social inclusion and therapy. Thus, this work reports the activities developed in a sensory garden installed at the Senador Helvidio Nunes de Barros Campus of the Federal University of Piauí in Picos - PI and its reflexes in the teaching-learning process. This garden is the result of the extension project “Botany in five senses” which is part of the Extension Program “Environmental Education at UFPI: dialogue between university and school for living with the semiarid region”. For this, the project is portrayed from its structuring, recruitment and training of academics, selection and spatial organization of plants and requesting schools to participate. Therefore, two basic points are delimited in this study: the lectures mediated in the university auditorium and the tours that took place in the sensorial garden between April 2018 and November 2019. In the practical reception activity in the sensorial garden, visitors were blindfolded so that they could explore the senses of touch and smell. In the meantime, observations of visitors' verbal and non-verbal communication, such as behavior, questioning, body expressions and comments, were manually noted. The records obtained in these approaches were analyzed qualitatively. It was concluded that the garden proved to be an efficient tool in environmental perception, awakening memories and instigating students to participate.